Altruism and Envy in Contests: An Evolutionarily Stable Symbiosis - Kai A. Konrad (Center for Economic Studies and ifo Institute (CESifo), 2002)
Altruists and envious people who meet in contests are symbionts. They do better than a population of narrowly rational individuals. If there are only altruists and envious individuals, a particular mixture of altruists and envious individuals is evolutionarily stable.
Keywords: 330; altruism; envy; contests; evolutionary stability